Establishment of Diagnostic Cutoff Points for Levels of Serum Antibodies to Pertussis Toxin, Filamentous Hemagglutinin, and Fimbriae in Adolescents and Adults in the United States - Baughman, Andrew L. (American Society for Microbiology, 2004)
Numerous reports have documented that serologic methods are much more sensitive than culture for the diagnosis of pertussis in adolescents and adults. However, a standardized serologic test for pertussis is not routinely available to most clinicians, and the serologic test levels or cutoff points correlated with diseases have not been determined. The goal of the present study was to examine the distribution of immunoglobulin G (IgG) levels against three Bordetella pertussis antigens (pertussis toxin [PT], filamentous hemagglutinin [FHA], and fimbria types 2 and 3 [FIM]) and to determine population-based antibody levels for the purpose of establishing such diagnostic cutoff points. Enzyme-linked immunosorbent assays (ELISAs) were performed with sera from >6,000 U.S. residents aged 6 to 49 years who participated in the Third National Health and Nutrition Examination Survey. Mixture models were developed to identify hypothesized exposure groups and establish diagnostic cutoffs. Quantifiable (>20 ELISA units/ml [EU]) anti-FHA and anti-FIM IgG antibodies were common (65 and 62% of individuals, respectively), but quantifiable anti-PT IgG antibodies were less frequent (16%). Given the distributions of antibody levels, an anti-PT IgG level of ≥94 EU was proposed as the diagnostic cutoff point. Application of this cutoff point to culture-confirmed illness in a prior study investigating cough illness yielded a high diagnostic sensitivity (80%) and specificity (93%). A standardized ELISA for anti-PT IgG with a single serum sample appears to be useful for the identification of recent B. pertussis infection in adolescents and adults with cough illness. The PT cutoff point will be further evaluated in prospective studies of confirmed B. pertussis infection.